STRATEGI MENINGKATKAN KOMPETENSI PENGAWAS UNTUK MEWUJUDKAN SEKOLAH BERMUTU DI SMP NEGERI 2 LOGHIA KABUPATEN MUNA - Alfian Hafis; Oktarina, Nina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
School quality is strongly influenced by the competence of school supervisors in conducting academic and managerial supervision. Therefore, developing supervisors' competencies is a strategic effort to improve educational quality. This study aimed to analyze the strategies for developing school supervisors' competencies to improve school quality at SMP Negeri 2 Loghia, including the supporting and inhibiting factors. A qualitative descriptive approach was employed. Informants included school supervisors, the principal, vice principals, teachers, and other stakeholders selected through purposive sampling. Data were collected through in-depth interviews, observations, and documentation, then analyzed using the interactive model of data reduction, data display, and conclusion drawing. Data validity was ensured through source, technique, and time triangulation. The findings indicate that competency development was implemented through academic and managerial supervision, professional guidance for teachers and principals, mentoring in instructional planning, monitoring and evaluation of school performance, and participation in education and training, workshops, and continuous professional development programs. These strategies contributed to improving teaching quality, strengthening school management, enhancing teacher professionalism, and achieving school quality standards. Supporting factors included the commitment of supervisors and principals, local government support, collaborative work culture, and professional development programs. The main obstacles were limited funding, wide supervisory coverage, limited supervision time, and inadequate facilities. These challenges were addressed through the use of information technology, prioritizing supervision activities, strengthening stakeholder coordination, and continuous competency improvement. Overall, sustainable and collaborative competency development strategies effectively supported school quality improvement at SMP Negeri 2 Loghia.